Исследования могильника Опушки в 2009 г. - Храпунов, И.Н.; Стоянова, А.А. (Археологічні дослідження в Україні, 2010)
Opushky burial ground is situated approximately 15 km to the south-east from Simferopol. Excavations there were conducted from 2003 to 2005, in 2007 and 2008. During this period 65 buri al structures were studied. In 2009, 16 burials were excavated including two crypts, eight undercut and six ground graves. The tombs researched belong to the Late Scythian and the Late Sarmatian cultures and are dated by the 2nd and 3rd centuries.